Socio-Cultural Practices as Barriers to Women Participation in Trade Union Activities in Nigeria - Adefolaju, Toyin (International Journal of Humanities and Social Science Research, 2016)
This paper examines the roles of Nigerian women in Trade Union activities by exploring the internal workings of five industrial unions in the country. Using a multi-stage random sampling technique, six hundred and forty workers were selected and they provided the data used for this study. Both questionnaire and in-depth interview methods were used to elicit information. The study reviews some literature, and reveals that despite their interest, a minuscule fraction of women workers actively participates in Trade Union activities in Nigeria due to a number of socio-cultural factors which inadvertently affect formal work place practices. Appropriate measures to ameliorate the situation are recommended.